(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the development and strategic importance of the transport system during World War II. It analyzes the role of logistics in supporting military operations through rail, road, sea, and air transport, backed by historical data and examples. Special focus is placed on the technological and organizational innovations in transport infrastructure that directly influenced the course and outcome of the war.